Massachusetts coverage expansion associated with reduction in primary care utilization among Medicare beneficiaries. - Bond, Amelia M; White, Chapin (Health Services Research, 2013)
Objective: To examine whether expanding coverage for the nonelderly affects primary care utilization among Medicare beneficiaries.Data Source: Zip code-level files from Dartmouth Atlas for Massachusetts and surrounding states, including Medicare utilization for 2005 (pre expansion) and 2007 (post expansion), and health insurance coverage for 2005.Study Design: We use two zip code-level outcomes: arc percent change in primary care visits per Medicare beneficiary per year, and percentage point change in the share of beneficiaries with one or more primary care visits. We use a regression-based difference-in-difference analysis that compares Massachusetts with surrounding states, and zip codes with high, medium, and low uninsurance rates in 2005. The 2005 uninsurance rates correspond to the size of Massachusetts' coverage expansion. We use propensity scores for identification of comparable zip codes and for weighting.Principal Findings: In areas of Massachusetts with the highest uninsurance rates-where insurance expansion had the largest impact-visits per beneficiary fell 6.9 percent (p < .001) relative to areas of Massachusetts with the smallest uninsurance rates.Conclusions: The expansion of coverage for the nonelderly reduced primary care visits, but it did not reduce the percent of beneficiaries with at least one visit. These results could imply restricted access, increased efficiency, or some blend.